Compartmental Glycosylation Flux Analysis. Issue 3 (2021) - Aggarwal, Shilpi; Qi, Xin; Neelamegham, Sriram; Gunawan, Rudiyanto
Abstract: N-linked glycosylation is a critical quality attribute of therapeutic monoclonal antibodies (mAbs) – an important class of biologics. In this work, we developed compartmental Glycosylation Flux Analysis (cGFA) to enable a more accurate representation of the cell's Golgi apparatus (GA), where protein glycosylation takes place, in the analysis of intracellular fluxes of glycosylation reactions. The application of one-compartment and two-compartment cGFA to a Chinese hamster ovary cell culture production of immunoglobulin G demonstrated the insufficiency of modeling the GA as one well-mixed compartment. The two-compartment cGFA was able to, not only fit the data significantly better than the one-compartment cGFA, but also accurately predict the localization of enzyme in the GA cisternae. Information on glycosylation alterations during cell cultivation, as provided by the cGFA, may lead to a better understanding of how different cell culture parameters control the N-linked glycosylation which would enable a more precise glycoengineering of therapeutic mAbs.